Predictors of Clinically Significant Postoperative Events After Open Craniosynostosis Surgery. Issue 4 (August 2016) - Goobie, Susan M.; Zurakowski, David; Proctor, Mark R.; Meara, John G.; Meier, Petra M.; Young, Vanessa J.; Rogers, Gary F.
Abstract : (Abstracted from Anesthesiology 122:1021–1032, 2015) Although procedures to correct craniosynostosis have become safer during the last 3 decades, most craniofacial centers still routinely admit patients to the intensive care unit (ICU) after major cranial vault procedures, as ICU admission provides an additional measure of safety after such large operations. However, ICU admission may be unnecessary for many patients, and bypassing it could decrease treatment costs, decompress ICU bed usage, and provide a more comfortable setting for the family.